Water and energy productivity in sprinkler irrigation systems under using groundwater - Ebrahimian, Hamed; Gholami, Zeynab; Noory, Hamideh (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Ver Resumen PDF.